Development of ornithological tourism in the Kresna Gorge – opportunity for conservation of the Griffon Vulture (Gyps fulvus) - Savova, Adelina; Berberova , Ralitza (Annual of Natural Sciences Department, 2022)
The Kresna Gorge attracts significant scientific ornithological interest as it is situated along one of the primary bird migration routes – Via Aristotelis. In 2010, a process of reintroducing the Griffon Vulture (Gyps fulvus) began in the area, which can now be deemed a success. However, there are still various anthropogenic factors that have a negative impact on the population’s resilience. The purpose of this study is to investigate the potential for developing ornithological tourism contributing to the protection of the local population of Griffon Vulture (Gyps fulvus).